Literary Analysis of the Story of the Nine-Tailed Dog for Creative Dan ce Phatom Phak - Atayaphan, Sudarat; Chiangkham, Theerawat; Khlainu, Nattawut; Thawongklang, Phakkapon; Tunkham, Juthamat; Yotha, Phitchayanan (Chophayom Journal, 2024)
The purpose of this research was to study the Literary analysis of the story of the Nine-tailed dog. The objective of the create choreography principles. This research aimed to: explore literature, specifically the Nine-Tailed Dog Story. This has been interpreted through a dance performance called the Pathomphak series. The instruments used were interviews. It is both structured and unstructured. The result of the study was presented by descriptive analytics. The result of this research found that the legend of Mae Posop (Goddess of Grain) which origined from the story of ninetailed dog. This was Thai and Chinese literature. The outstanding characteristic of the nine-tailed dog was kind and helpful. The story told that the nine-tailed dog stole some food from the heaven by dipping his tail into the pile of rice, then came down to the earth, and gave the rice to humans. In the ancient time, Mae Posop made the fertile land, so humans worshiped her until the present. This led to create the choreography related to this phenomenon. The researchers used the Thai dance principle to determine the concept, process the data, determine the scope and elements. These elements are costumes, music and a dancing performance. The researchers used them to create the the beautiful and aesthetic choreography called the "Pathomphak" series. were dog-shaped lines on many cliff shelters and cave walls. For example, at Lat Bua Khao Subdistrict, Sikhio District, Nakhon Ratchasima Province. In this study, the researcher applied the principles of artificial intelligence to the field of cognitive thinking. In data processing, scoping involves defining information and determining other elements including costumes, music, and dance procedures. Previously used to generate artificial dance pieces, it evolved into a form of creative performance. Exploring the concepts and theories of aesthetics in dance. Keywords: Pathomphak, literature, stories telling, nine-tailed do